Essays in theoretical physics : in honour of Dirk ter Haar - Haar, D. ter; Parry, W. E. (William Edward) (Pergamon Press, 1984)
Essays in Theoretical Physics: In Honour of Dirk ter Haar is devoted to Dirk ter Haar, detailing the breadth of Dirk's interest in physics. The book contains 15 chapters, with some chapters elucidating stellar dynamics with non-classical integrals; a mean-field treatment of charge density waves in a strong magnetic field; electrodynamics of two-dimensional (surface) superconductors; and the Bethe Ansatz and exact solutions of the Kondo and related magnetic impurity models. Other chapters focus on probing the interiors of neutron stars; macroscopic quantum tunneling; unitary transformation meth.